Neuro-Ophthalmologic Complications of Giant Cell Arteritis: Diagnosis and Treatment - Fein, Alexander S.; Ko, Melissa W. (Seminars in Neurology, 2019)
Giant cell arteritis (GCA) is the most common vasculitis in individuals 50 years or older, with a lifetime risk in the United States of 1% in women and 0.5% in men. It is a granulomatous disease that affects large- and medium-sized vessels, most notably the branches of the internal and external carotid arteries. GCA can cause both afferent and efferent visual manifestations, the most common being arteritic anterior ischemic optic neuropathy. Diagnosis of GCA is made using criteria developed by the American College of Rheumatology, which include clinical signs, positive biopsy, and elevated erythrocyte sedimentation rate. C-reactive protein and platelet counts may be elevated in GCA, and noninvasive imaging modalities such as Doppler ultrasound and magnetic resonance imaging are now being used to aid in diagnosis. While glucocorticoids are the mainstay of treatment for GCA, new breakthrough treatments such as tocilizumab (an anti-IL-6 receptor antibody) have shown great promise in causing disease remission and reducing the cumulative glucocorticoid dose. Emerging therapies such as abatacept and ustekinumab are still being studied and may be of use to clinicians in the future.
Keywords: giant cell arteritis; temporal arteritis; treatment; diagnosis; neuro-ophthalmology